2018
DOI: 10.15343/0104-7809.20184201248265
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Disorders In Countryside Fishermen Of Amazonas-Brazil

Abstract: The postures adopted during fishing work can increase the rise of pain and discomfort, worsening the health risks of fishermen. To identify the prevalence of musculoskeletal disorders in fishermen working in the interior of the State of Amazonas, Brazil. A descriptive cross-sectional study was conducted in the fishery sector in the city Coari AM (SINPESCA). The Nordic Musculoskeletal Questionnaire (QNM) and the Couto Checklist were applied. Of the 40 fishermen, the most affected areas by musculoskeletal disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
2
4
0
1
Order By: Relevance
“…For Ramiser-Maestre [ 54 ], it is necessary to evaluate the perception of pain through a biopsychological model, especially when considering analysis by gender; in this way, the study cited [ 52 ] suggests that women have high pain perception, but better adapt to chronic pain, and as a consequence, have better functional capacity in relation to daily activities. In the findings of this study, it can be observed that 92.5% of artisanal fishermen reported musculoskeletal pain in at least one region of their bodies over the last year, the most afflicted parts being the regions of the wrist/hand, upper and lower back, which is closer to the findings of other scientific investigations [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…For Ramiser-Maestre [ 54 ], it is necessary to evaluate the perception of pain through a biopsychological model, especially when considering analysis by gender; in this way, the study cited [ 52 ] suggests that women have high pain perception, but better adapt to chronic pain, and as a consequence, have better functional capacity in relation to daily activities. In the findings of this study, it can be observed that 92.5% of artisanal fishermen reported musculoskeletal pain in at least one region of their bodies over the last year, the most afflicted parts being the regions of the wrist/hand, upper and lower back, which is closer to the findings of other scientific investigations [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 87%
“…Descriptively, there is a higher prevalence of MSD in shellfish gatherers, very similar to previous studies performed in the Brazilian northeast, in which the authors also found a high prevalence of generalized MSD [ 35 ] among shellfish gatherers, as well as pain in the upper limbs [ 45 ], lower back region [ 45 ], all related to the practice of fishing [ 34 ]. Evidence of MSD symptoms were also found in studies with fishermen, for example in the United States (42.8–83.3%) [ 16 ], Turkey (84%) [ 17 ], Norway (33%) [ 19 ] and Spain (65.5–88%) [ 24 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Estudos vêm sendo desenvolvidos objetivando compreender o trabalho e as queixas musculoesqueléticas. No entanto, é necessário considerar a incipiência na literatura científica sobre tais distúrbios no trabalho informal, inclusive no processo de trabalho da catadora de marisco 6,11,12 .…”
Section: Introductionunclassified